2012
DOI: 10.1387/ijdb.120142pk
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of germ cell meiosis in the fetal ovary

Abstract: Fertility depends on correct regulation of meiosis, the special form of cell division that gives rise to haploid gametes. In female mammals, germ cells enter meiosis during fetal ovarian development, while germ cells in males avoid entering meiosis until puberty. Decades of research have shown that meiotic entry, and germ cell sex determination, are not initiated intrinsically within the germ cells. Instead, meiosis is induced by signals produced by the surrounding somatic cells. More recently, retinoic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 114 publications
(150 reference statements)
1
28
1
Order By: Relevance
“…4c-e and Supplementary Tables 1 and 2). In accordance with female E13.5 PGCs preparing to initiate meiosis I and male PGCs undergoing mitotic arrest 22,23 Supplementary Fig. 8 and Supplementary Tables 1 and 2).…”
Section: Resultssupporting
confidence: 55%
“…4c-e and Supplementary Tables 1 and 2). In accordance with female E13.5 PGCs preparing to initiate meiosis I and male PGCs undergoing mitotic arrest 22,23 Supplementary Fig. 8 and Supplementary Tables 1 and 2).…”
Section: Resultssupporting
confidence: 55%
“…Indeed, RARE-lacZ expression is not detected in ovary during these stages, although it is easily detected in mesonephros and completely absent in the mesonephros of Raldh2 −/− ; Raldh3 −/− mice (6). The sensitivity of RARE-lacZ had previously come into question (9), but recent studies have shown that RARE-lacZ is sensitive to 0.25 nM RA (10), lower than the 1 nM concentration shown to marginally induce meiosis in isolated PGCs and much lower than the 10 nM concentration needed for more complete meiotic induction in the dose-response curve (9). …”
mentioning
confidence: 99%
“…The female embryo is quite different from the male. The developing ovary is relatively quiescent compared to the male testis, and the female reproductive organs and genitalia form in the absence of exposure to testosterone and AMH [Reviewed in (Capel, 1996; Kashimada and Koopman, 2010; Spiller et al, 2012)]. These differences between the sexes in normal development underscore the potential for the genitals and the brain to be highly sensitive to developmental perturbations by EDCs.…”
Section: Development Of Reproductive Neuroendocrine Circuitrymentioning
confidence: 99%